1993
DOI: 10.2527/1993.71112986x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of porcine somatotropin and dietary lysine on growth performance and carcass characteristics of finishing swine fed to 105 or 127 kilograms2

Abstract: One hundred twenty barrows (initially 59 kg) were used to determine the effects of dietary lysine and porcine somatotropin (pST) on growth performance and carcass characteristics of finishing pigs fed to heavy market weights (127 kg). Pigs were injected daily with either 4 mg of pST or a placebo and fed diets containing either .8, 1.0, 1.2, or 1.4% lysine in a 2 x 4 factorial arrangement. Performance data were collected and evaluated for the weight ranges: 59 to 105, 105 to 127, and 59 to 127 kg. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 0 publications
2
13
0
2
Order By: Relevance
“…The effects of slaughter age. Age at slaughter did not affect growth rate which agrees with Johnston et al (1993) and Candek-Potokar et al (1998) with pigs from 100 to 130 kg body weight (BW). However, Albar et al (1990) with castrates and gilts of similar weights reported that daily gains decreased with age.…”
Section: Discussionsupporting
confidence: 56%
“…The effects of slaughter age. Age at slaughter did not affect growth rate which agrees with Johnston et al (1993) and Candek-Potokar et al (1998) with pigs from 100 to 130 kg body weight (BW). However, Albar et al (1990) with castrates and gilts of similar weights reported that daily gains decreased with age.…”
Section: Discussionsupporting
confidence: 56%
“…It was shown previously that pST treatment increases the efficiency with which nutrients are used for muscle mass gain by redistributing nutrients from fat to muscle (5,6,17,19,35,48). Treatment with pST has been shown to increase whole body (24,47) and skeletal muscle (5,33,45) protein synthesis rates; however, the mechanism through which this occurs is unknown. Previous studies conducted in our laboratory have shown that pST increases muscle protein synthesis in the fed state but not in the fasted state (2).…”
Section: Discussionmentioning
confidence: 94%
“…Very few researchers have measured the effects of dietary lysine and pST on protein deposition in heavy pigs. In one such study, Johnston et al (1993) offered diets ranging from 8 to 14 g lysine/kg to barrows treated with pST (4 mg/d) over the live weight ranges of 59 to 105 kg and 105 to 127 kg. Increasing dietary lysine increased protein deposition in a quadratic manner (P = 0.08) between 59 and 105 kg and linearly (P < 0.01) between 105 and 127 kg.…”
Section: Resultsmentioning
confidence: 99%